2017
DOI: 10.18585/inabj.v9i1.212
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Alpinia galanga Rhizome Crude Extract on NIH-3T3 Cells

Abstract: B ACKGROUND:Alpinia galanga (A. galanga) was reported as a potential medicinal source due to its wide effect. A. galanga rhizome crude extract (ARCE) was reported to have high cytotoxic effect in cancer cells, but low in normal cells. However half maximal inhibitory concentration (IC 50 ) of ARCE is not clearly known yet. Hence, current study was conducted to investigate the IC 50 of ARCE in normal standard fibroblast cell line, NIH-3T3 cells. METHODS:Rhizomes of A. galanga were collected, peeled, dried, mille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Each cell line was cultured in a suitable medium to obtain the desired growth, and the growth curve of the cell line was plotted. The cytotoxicity of the leaf extracts was evaluated by treating the NIH/3T3 cell line with the 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide solution (MTT assay) according to a method described elsewhere [ 71 ]. The NIH/3T3 cells (at a density of 6 × 10 3 per well 100 mL of the medium) were grown in a 96-well microtitration plate.…”
Section: Methodsmentioning
confidence: 99%
“…Each cell line was cultured in a suitable medium to obtain the desired growth, and the growth curve of the cell line was plotted. The cytotoxicity of the leaf extracts was evaluated by treating the NIH/3T3 cell line with the 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide solution (MTT assay) according to a method described elsewhere [ 71 ]. The NIH/3T3 cells (at a density of 6 × 10 3 per well 100 mL of the medium) were grown in a 96-well microtitration plate.…”
Section: Methodsmentioning
confidence: 99%
“…The ethanolic extract of A. galanga had a very high IC50 value against NIH-3T3 fibroblast cells. The IC50 values for these cells reached 620.5 ug/ml for 24 h and 666.6 ug/ml for 48 h. A high value indicates that the content in the ethanolic extract of A. galanga tends to be safe for normal human cells [20].…”
Section: Resultsmentioning
confidence: 90%
“…However, when it was co‐administered with NP 800 μg/ml dosage, the overall survival of our cell line was increased, suggesting that although when administered alone, the 500 μg/ml dosage of ALP extract was cytotoxic, co‐administration with NP could balance its cytotoxic effects, and as a result, increasing the overall viability of fibroblasts. It has been observed that IC 50 of Alpinia galanga rhizome crude extract in 24 and 48 hr of treatment was 620.5 µg/ml and 666.6 µg/ml, respectively, on fibroblast cell lines (Sandra et al., 2017). Norbert Lucak et al showed that NP treatment with different concentrations 1, 10, 100 and 200 µg/ml significantly reduced spermatozoa cell viability, and the lowest survival of spermatozoa was determined after NP treatment at the concentration of 200 µg/ml, which indicates that NP can have a severely toxic effect on the reproductive system (Lukac et al., 2013).…”
Section: Discussionmentioning
confidence: 99%